Prevalensi nematoda gastrointestinal pada sapi di Pasar Ternak Payakumbuh - Delli Lefiana; Dihan Kurnia (Agrivet : Jurnal Ilmu-Ilmu Pertanian dan Peternakan (Journal of Agricultural Sciences and Veteriner), 2024)
This study aimed to determine the prevalence of Nematoda infection in the gastrointestinal tract of cattle at Payakumbuh Cattle Market. The research was conducted in August 2020. The method used was a survey using purposive sampling. One hundred fifty-five cow dung samples were collected from the Payakumbuh Cattle Market. The fecal examination was performed using the flotation method and sedimentation method. The gastrointestinal nematode was Strongyloides sp, Ostertagia sp., and Trichuris sp. Infection with one roundworm species in 18.46% of cows and 24% of bulls. Infection with two roundworm species in 10% of cows and 20% bulls. Infection with three roundworm species in 2.3% in cows and 4% in bulls. The prevalence of three roundworm species was 0.77% in cows and not found in bulls. The rate of nematode infection in the 0-2-year-old group was 29.16%, and the > two-year-old group was 33.73%. It can be concluded that the average cattle in the Payakumbuh Cattle Market are infected with gastrointestinal nematodes, and severe treatment is needed either by farmers or by involvement from the local government.